The implementation of reinforcement or students Positive motivation to improve learning activeness Inppknon the third class in sd negeri 49 limau Manis kulam - Gusni Gusni (Jurnal Ilmiah Pendidikan Scholastic, 2017)
n order to learn a lesson well, we need to hear, see, ask questions about it, and discuss it with others. Not only that, teachers need to "do", which describe something in their own way, showing for example, tried to practice skills and tasks that require p What Knowledge they have earned. Problems to be studied in this research are: 1) pakah using strengthening model can improve the learning result of class III State Elementary School 49 Limau Manis Kulam the school year 2016 - 2017? 2).The steps taken in using the reinforcement model in the PPKN lessons of the third grade students of SD? From the results of learning activities that have been done for three cycles, and based on all the discussion and analysis that has been done can be generated: 1). Learningbyteaching reinforcement learning in Civics Has a positive impact in improving student achievement which is marked by the improvement of students' learning mastery in every cycle, that is cycle I (62,50%), cycle II (75,00%), cycle III (87,50%). 2) Implementation of an instructional faculty reinforcement Have a positive influence, that is can improve student's motivation to learn the lesson of Civics shown with average responses of the students stating that students are interested in and are interested in learning teaching Civics So they become motivated to learn. This technique is used to extract some of the written data sourced from school reports and matters that can support this research. This technique is used to obtain information from teachers regarding the provision of reinforcement in the learning process. Observation technique is used to obtain data on preparation of teaching of Civic Education teacher (Civics) and the implementation of teachers in the process of learning in this class This technique is the main technique because the use of questionnaire is expected to obtain most of the required data, ie by using written question items given to